KARAKTERISTIK SOSIAL EKONOMI MASYARAKAT PETANI KECAMATAN BANDAR DALAM SISTEM LIVELIHOOD PEDESAAN - M Rosyid; Iwan Rudiarto (Geoplanning: Journal of Geomatics and Planning, 2014)
Socio-economic position in terms of development generally  to see how big the level of well-being of an area where it can be seen from the potential and the resources therein. Bandar distrit is rural areas with geographical condition of the mountains and a good watering with is dominated by the agricultural sector (35% of the total areadistricts) can be found that most of the people working with depends on the utilization of natural resources. Not only that the quality of human resources became milestones in the progress of development.The purpose of this research is to identify the characteristics of the social and economic conditions of society rural farmers in rural Livelihood systems associated with education, income and the type of activities to the resources in Bandar. By using a quantitative approach supported by spatial analysis has focused on the potential, problems, and the amount of ownership of community resources. In the system of Livelihood, is divided into five socio-economic livelihood assets where power access owned by Bandar Sub-district has a maximum value of human resources, subsequently followed by physical capital and natural resources capital.While the condition of two other assets that financial and social capital only has a value that is less than maximum/lower. It is characterized by a low level ofeducation, low-income family per capita income amounting to Rp. 5.399.345 per year or were under the standard earnings Batang are mostly subsistence farmers patterned or does not make the commercial fields as agriculture and lacking the proper functioning of social groups in both averaging – align the farming community are below the poverty line. Later research is expected to provide a source of information and knowledge about the patterns of resource utilization and socio economic characteristics in Bandar describing existing condition so that the country can be used as a reference and referral information to further research